Analysis of the Relationship between Family Support and Tuberculosis Treatment Compliance in Seumirah Village, Nisam Antara, North Aceh, Aceh: Analisis Hubungan Dukungan Keluarga dengan Kepatuhan Pengobatan Tuberkulosis di Desa Seumirah, Nisam Antara, Aceh Utara, Aceh - Yahya, Khairuman; Ramah Bengi, Mareni; Putri Diana, Reva; Pohan, Saidah; Muna Putri, Shelvy; Devika, Fitri; Sarah, Atikah (Medical : Jurnal Kesehatan dan Kedokteran, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and is one of the main health problems in Indonesia. In 2023, Indonesia reported 969,000 new cases of TB with a mortality rate reaching 93,000 per year (WHO, 2023). The level of adherence to TB treatment is still low, which is an obstacle in efforts to control this disease. This study aims to analyze the relationship between family support and the level of adherence to TB treatment in Seumirah Village, an area with high socio-economic challenges and stigma against TB. This study used a cross-sectional approach: qualitative data were obtained through in-depth interviews and focus group discussions, while quantitative data were analyzed using the Spearman correlation test (non-parametric) on 50 respondents. The results showed a significant positive correlation between family support and adherence to treatment (correlation coefficient r = 0.72, p < 0.01). The coefficient of determination (R² = 51.84%) indicates that family support explains 51.84% of the variation in adherence to treatment. The main influencing factors are the level of family knowledge, social stigma, and access to health facilities. The conclusion shows that family support significantly contributes to increasing adherence to TB treatment in patients. The higher the level of family support, the greater the patient's adherence in completing treatment. These findings emphasize the importance of family-based interventions and increasing community education to support the success of TB treatment.